2020
DOI: 10.1080/17483107.2020.1830442
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of appropriate paper-based technology for Kenyan children with cerebral palsy

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
16

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 47 publications
0
29
0
16
Order By: Relevance
“…According to our caregivers, the inefficiency of political, social and structural support and ableism harmed the participation and recognition of children with CZS in society. These aspects are also observed in children with disabilities from low‐to‐middle income countries 36 …”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…According to our caregivers, the inefficiency of political, social and structural support and ableism harmed the participation and recognition of children with CZS in society. These aspects are also observed in children with disabilities from low‐to‐middle income countries 36 …”
Section: Discussionmentioning
confidence: 78%
“…These aspects are also observed in children with disabilities from low-tomiddle income countries. 36 Another finding highlighted the difficulty in accessing specialized rehabilitation intervention for children with CZS, such as the Padovan ® , Bobath ® and Pediasuit ® methods. Caregivers who had access to intensive intervention with the use of therapeutic suits reported improvements in their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assisted technologies such as hearing aids, cochlear implants, communication boards, eye tracking devices, and simple aids to daily living such as wheelchairs and grab bars are not readily available in many LMICs ( 117 , 118 ). Early intervention with physical and occupational therapies, as early as infancy, have the potential to improve developmental opportunities for at-risk patients ( 117 , 119 ). Developmental clinics with multidisciplinary care teams should be in place to follow these children over time in an organized fashion.…”
Section: Opportunities For Future Stepsmentioning
confidence: 99%
“…47 School therapists also reported increased self-esteem, social interaction, and access to activities. 72 A study evaluating the use of paper-based technologies in Kenya 117 did not separate sitting and standing devices in the quantitative analysis, but noted, regarding stander use, improvement in hand use, ability to reach and change position, and improved independent feeding abilities. Caregivers also reported that the stander reduced burden of care and allowed the child to play safely and independently or with other children while the parent was engaged in household or other chores.…”
Section: Supported Standing Provides An Important Position Change And...mentioning
confidence: 99%